Architectural Design Capstone - Bhate, Anushka Anand (My University, 2025)
This Signature Honors Project is a portfolio-based creative endeavor that integrates coursework from DESN 3010 (Reality Capture) and DESN 4700 (Capstone) to explore the intersection of digital design tools and architectural problem-solving. The portfolio showcases a series of projects that apply photogrammetry, 3D modeling, and visualization techniques to address site-specific, user-centered design challenges. These include adaptive reuse proposals, environmentally responsive shelters, and a comprehensive final capstone: a luxury island resort with suites, villas, and shared amenities. Drawing on principles of human-centered design, sustainability, and biomimicry, the work highlights how tools like Revit, SketchUp, AutoCAD, and Lumion can be used to create context-driven, regenerative solutions. Beyond demonstrating technical proficiency, the portfolio reflects the evolution of my architectural voice and supports my long-term goal of designing patient-centered healthcare environments.
Keywords: architecture; sustainable design; digital visualization